ANALYSIS OF THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP AND INNOVATION CULTURE ON EMPLOYEE PERFORMANCE WITH ORGANIZATIONAL COMMITMENT AS AN INTERVENING VARIABLE AT PT. ASIA SAKTI WAHID FOODS MANUFACTURES - Herbert Angkasa; Darwin Lie; Hendry (Sekolah Tinggi Ilmu Ekonomi Sultan Agung Pematangsiantar, 2026)
This study aims to analyze the influence of transformational leadership and innovation culture on employee performance, with organizational commitment as a mediating variable at PT Asia Sakti Wahid Foods Manufactures. The method used is quantitative with a SmartPLS-SEM approach involving 70 respondents. The results show that transformational leadership and innovation culture have a positive and significant effect on employee performance, both directly and indirectly through organizational commitment as a mediator. This study highlights the importance of implementing transformational leadership and strengthening innovation culture to enhance organizational commitment and optimize employee performance.